Evaluation of the Volleyball Sports Achievement Development Program at STIKIP Modern Ngawi - Siti Hardianti; Rachmah Laksmi Ambardini; Firdaus Nuransyari; Neneng Hidayat (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Volleyball UKM STKIP Modern Ngawi is a UKM that still needs evaluation to find out the strengths and weaknesses in the achievement coaching program and the extent to which the existing achievement coaching program has achieved the set goals. the purpose of this study was to evaluate the achievement coaching program in volleyball UKM STKIP Modern Ngawi. This research is an evaluation study using the Context, Input, Process and Product (CIPP) evaluation model. The subjects in the study were 20 people consisting of 15 athletes, 3 administrators, and 2 coaches of Volleyball UKM STIKIP Modern Ngawi. Data collection techniques in this study used observation, interviews, questionnaires, and documentation. Data analysis techniques use descriptive analysis, both quantitative and qualitative. The results of the research on the evaluation of the achievement coaching program for volleyball UKM STKIP Modern Ngawi athletes in terms of Context, the background of the coaching program stated quite well (2.75), the purpose of the coaching program stated quite well (2.46), the coaching program stated that it was good (3.63). The results of Input evaluation research on the achievement coaching program for volleyball UKM STKIP Modern Ngawi explain that funding in volleyball UKM Stikip Modern Ngawi is very good (4.05). but the problem of facilities and infrastructure is still lacking (1.47). The results of Process evaluation research on the achievement coaching program for volleyball UKM STKIP Modern Ngawi, the training and coaching program is quite good, and the implementation of monitoring and evaluation states that it is very good (4.00). The results of Product evaluation research on the achievement coaching program of the STKIP Modern Ngawi volleyball UKM based on the statements of administrators, coaches and athletes are quite good (2.14). The results of evaluation research based on the statements of administrators, coaches and athletes in the volleyball UKM STKIP Modern Ngawi in terms of Context, Input, Process and Product can be concluded quite well.